SLOW GROWTH IN VITRO CULTURE FOR CONSERVATION OF HANCORNIA SPECIOSA GOMES - Oliveira, Kívia Soares de; Aloufa, Magdi Ahmed Ibrahim (Floresta, 2022)
Hancornia speciosa Gomes is a fruit species endemic to the Cerrado and coastal plains of Northeast of Brazil, with great economic, nutritional, ecological, and medicinal potential. This study aimed to evaluate the effect of sorbitol and sucrose as osmotic regulators on the in vitro growth of mangabeira, aiming at conservation by slow growth. The explants were obtained from in vitro germinated seedlings and inoculated in MS medium supplemented with sucrose (15 and 30 g L-1) and sorbitol (0, 5, 10 and 15 g L-1). The experimental design was completely randomized with 20 repetitions in a 4 x 2 factorial arrangement (sorbitol x sucrose concentrations). The evaluations were performed at 30, 60 90 and 120 days of incubation. The analyzed variables were number of nodes/budding, number of leaves, leaf abscission, leaf color and survival of explants. The data were statistically analyzed by generalized linear model analysis. The results indicated a significant difference between the osmotic regulators and the culture time for all variables. Sorbitol showed a more pronounced growth-reducing effect than sucrose. The use of 30 g L-1 sucrose combined with 10 or 20 g L-1 sorbitol reduced the growth in a critical way, making it clear that the water stress caused was not tolerated by the plants, negatively interfering in its development. Treatment with 15 g L-1 sucrose combined with 5 g L-1 sorbitol promoted the best result, allowing the conservation of plants for 120 days.